Simulation of venting and leaks from pressure vessels - Kanes, Rym; Basha, Alisha; Véchot, Luc N.; Castier, Marcelo (Journal of loss prevention in the process industries, 2016)
Several industrial disasters involve accidental releases of hazardous chemicals from ruptured vessels. On other occasions, intentional releases avoid catastrophic events, as in the venting of vessels with runaway reactions. Such releases can be a single phase or multiphase release, choked or non-choked. To assess their potential hazards, it is important to estimate the flow rate and properties of the discharged fluid, but both change with time during the leaking process. Several models exist to simulate accidental releases, often based on assumptions that increase the uncertainty of their predictions when applied to high-pressure vessels. This work takes a different approach by using rigorous thermodynamic procedures to: (1) find the state of fluid within the vessel using a flash algorithm for systems of specified internal energy (U), volume (V), and mole numbers of each component (N); (2) track phase appearance and disappearance in the vessel; (3) find the state of fluid as it exits the vessel, assuming the leaking point is the throat of an adiabatic, converging nozzle that operates isentropically; (4) compute sound speeds in multiphase systems to establish whether the leak flow is choked. The same equation of state is consistently used to estimate the thermodynamic properties in these procedures. The results of the computational code that implements these steps are generally in good agreement with experimental data and simulation results from the literature. •Simulations of leaks and venting operations from pressure vessels use rigorous thermodynamic methods.•State of fluid in vessel found with flash algorithm for systems of given internal energy, volume, and component amounts.•Procedure tracks phase appearance and disappearance in the vessel.•Sound speed calculations in multiphase systems are evaluated rigorously.•Results are in good agreement with experimental data and simulation results from the literature.